How advanced are we on the consequences of oral exposure to food contaminants on the occurrence of chronic non communicable diseases?. (September 2022) - Grados, Lucien; Pérot, Maxime; Barbezier, Nicolas; Delayre-Orthez, Carine; Bach, Véronique; Fumery, Mathurin; Anton, Pauline M.; Gay-Quéheillard, Jérôme
Abstract: The development of an individual during fetal life and childhood is characterized by rapid growth as well as gradual maturation of organs and systems. Beyond the nutritional intake in essential nutrients, food contaminants can permanently influence the way organs mature and function. These processes are called "programming" and play an essential role in the occurrence of non-communicable chronic diseases throughout the lifespan. Populations as pregnant women, fetuses and young children are vulnerable and particularly sensitive to food contaminants which can induce epigenetic modifications transmissible to future generations. Among these contaminants, pesticides are found in most food matrices exposing humans to cocktails of molecules through variable concentrations and duration of exposure. The Maillard reaction products (MRPs) represent other food contaminants resulting from heat treatment of food. Modern diet, rich in fats and sugars, is also rich in neoformed pathogenic compounds, Advanced Glycation End products (AGEs), the levels of which depend on the heat treatment of foods and eating habits and whose effects on health are controversial. In this review, we have chosen to present the current knowledge on the impacts of selected pesticides and MRPs, on the risk of developing during life non-communicable chronic diseases such as IBD, metabolic disorders or allergies. A large review of literature was performed via Pubmed, and the most appropriate studies were summarised. Highlights: Development during fetal life and infancy is characterized by rapid growth as well as maturation of organs and systems. Diet contains numerous environmental contaminants (residues, neoformed compounds) that could contribute to the appearance of CNCD. Food contaminants may permanently influence the way these organs mature and function, a process called "programming". Programming plays an important role in the occurrence of CNCD and the early life period is a window particularly sensitive to food contaminants. Some contaminants may alter the programmed expression of some genes, resulting in effective remodeling of tissue structure and functionality.